Impact of early life geohelminths on wheeze, asthma and atopy in Ecuadorian children at 8 years. Issue 9 (7th April 2021) - Cooper, Philip J.; Chis Ster, Irina; Chico, Martha E.; Vaca, Maritza; Oviedo, Yisela; Maldonado, Augusto; Barreto, Mauricio L.; Platts‐Mills, Thomas A. E.; Strachan, David P.
Abstract: Background: Early‐life exposures to geohelminths may protect against development of wheeze/asthma and atopy. Objective: To study the effect of maternal geohelminths and infections in children during the first 5 years on atopy, wheeze/asthma and airways reactivity/inflammation at 8 years. Methods: Birth cohort of 2404 neonates followed to 8 years in rural Ecuador. Data on wheeze/asthma were collected by questionnaire and atopy by skin prick test (SPT) reactivity to 9 allergens. We measured airways reactivity to bronchodilator, fractional exhaled nitric oxide (FeNO) and nasal eosinophilia. Stool samples were examined for geohelminths by microscopy. Results: 1933 (80.4%) children were evaluated at 8 years. Geohelminths were detected in 45.8% of mothers and 45.5% of children to 5 years. Frequencies of outcomes at 8 years were as follows: wheeze (6.6%), asthma between 5 and 8 years (7.9%), SPT (14.7%), airways reactivity (10%) and elevated FeNO (10.3%) and nasal eosinophilia (9.2%). Any maternal geohelminth was associated with reduced SPT prevalence (OR 0.72). Childhood Trichuris trichiura infections during the first 5 years were associated with reduced wheeze (OR 0.57) but greater parasite burdens with Ascaris lumbricoides at 5 years were associated with increased wheeze (OR 2.83) and asthma (OR 2.60). Associations between maternal geohelminths and wheeze/asthma were modified by atopy. Parasite‐specific effects on wheeze/asthma and airways reactivity and inflammation were observed in non‐atopic children. Conclusions: Our data provide novel evidence for persistent effects of in utero geohelminth exposures on childhood atopy but highlight the complex nature of the relationship between geohelminths and the airways. Registered as an observational study (ISRCTN41239086). Abstract : Maternal geohelminths protect 8‐year‐old children from the development of allergen skin prick test reactivity with strongest effects observed in infected children of infected mothers. Early childhood infections with Trichuris trichiura protect against wheeze at 8 years. Effects of geohelminths on wheeze/asthma and airways reactivity and inflammation at 8 years vary by parasite species and atopy.